What psoriasis can hide - Salmón-González Z; R Herreras-Martínez; M Latorre-Asensio; S Nieto; C Garilleti; MS Rodríguez Duque (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2023)
Alpha-1 antitrypsin deficiency (DAAT) is a genetic disorder that manifests as pulmonary emphysema, liver cirrhosis, and, rarely, as the skin disease panniculitis [1], but other rare skin manifestations had been described previously in literature [2]. Despite being one of the most frequent genetic diseases, professionals need high clinical suspicion for its diagnosis.